Film dialogue - Jaeckle, Jeff; Kozloff, Sarah (Wallflower Press, 2013)
"Film Dialogue is the first anthology in film studies devoted to the topic of language in cinema, bringing together leading and emerging scholars to discuss the aesthetic, narrative and ideological dimensions of film speech that have largely gone unappreciated and unheard. Consisting of insightful essays that divide into sections on genre, auteur theory and cultural representation, this collection revisits and reconfigures several of the most established topics in film studies in an effort to persuade readers that 'spectators' are also 'audiences,' that looking has its equal in listening, and that images are best understood and appreciated through their interactions with words. With an introduction that outlines a methodology of film dialogue study, Film Dialogue is a welcome addition to ongoing debates about the place, value and purpose of language in cinema."--Page [4] of cover.